PHILOLOGY AS A SCIENTIFIC AND EDUCATIONAL PROJECT - Pavel P. Shkarenkov (Высшее образование в России)
The article focuses on philology as a scientific and educational project realized at the Institute of Philology and History of the Russian State University for the Humanities (RSUH). The most important impetus to the creation and subsequent development of philological education in the RSUH was the idea of the fruitfulness of the comparative approach to the content of the educational process and to the research work supplying this content as well as the necessity to actualize the logic of the «general and special» in the formation of ideas about the development of culture and civilization. The institutionalization of comparative studies as a complex specialization - not only for philologists but also for historians, translators, theatre and cinema critics and experts - has already proven its heuristic value and educational effectiveness over the years.